Factors predicting peripheral blood progenitor cell mobilization in healthy donors in the era of related alternative donors: Experience from a single center. Issue 4 (29th January 2019) - Bailén, Rebeca; Pérez‐Corral, Ana María; Pascual, Cristina; Kwon, Mi; Serrano, David; Gayoso, Jorge; Balsalobre, Pascual; Muñoz, Cristina; Díez‐Martín, José Luis; Anguita, Javier
Abstract : Background: Poor mobilization results are unexpected after G‐CSF‐induced peripheral blood stem cell collection in healthy donors. However, 2%‐5% of the donors are poor mobilizers. Factors predicting CD34+‐cell yield after mobilization in related alternative donors are still poorly known. Patients and methods: Baseline characteristics and efficacy results of G‐CSF induced mobilization of 159 adult healthy donors in our institution from 2008 to 2016 were retrospectively analyzed. All donors received 10 μg/kg of G‐CSF once a day subcutaneously for 4 days. Leukapheresis started on the 5th day of G‐CSF treatment. Donors were classified as poor mobilizers if they had less than 20 000 CD34 + cell/mL peripheral blood count in the 5th day of G‐CSF treatment or if they needed three or more leukapheresis for graft collection. Results: Age, weight, and platelet count before and after mobilization were significantly different between poor and good mobilizers. Poor mobilizers ( n = 16) were older (50.6 vs 41.7 years, P = 0.002), weight lower (64 vs 75 kg, P = 0.00) and showed a lower platelet count before (199.5 vs 219.0 × 10 9 /L, P = 0.03) and after (192.5 vs 206 × 10 9 /L, P = 0.019) mobilization. In the multivariate analysis only the 30% of the variability of mobilization was explained by the model (sensitivity 80%, specificity 70%). Conclusion: In this cohort of healthy donors in a single institution, older age, less weight, and lower platelet count was associated with poorer mobilization. With clinical and analytic factors it is not possible to predict more than 30% of the variability. Further studies are needed to investigate new variables.